The Effect of Characteristics of The Board of Commissioners and Audit Committee on The Level Of Accounting Conservatism - Mentari Puteri Pertiwi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
Accounting conservatism is frequently with reliable reporting in the past and auditor behavior. Shareholders are required to be more available with public, that’s where the role of accounting conservatism can support the credibility of conservative disclosure of information. This research using multiple regression method, the data used is secondary data from the company’s annual report. The population of this study is a Manufacturing Company listed on the Indonesia Stock Exchange in 2009-2011, The sample used is 33 companies. From the results of the study, it was concluded that the characteristics of the board of commissioners had no significant effect on accounting conservatism, while indicators of the audit committee such as the size of the audit committee, the frequency of committee meetings, and the competence of the audit committee had a significant effect on accounting conservatism.